2024
DOI: 10.1037/cdp0000528
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal associations of perceived discrimination, internalizing symptoms, and academic achievement in Latino students across the college transition.

Abstract: Objective: Despite growing evidence that perceived discrimination negatively impacts underrepresented ethnic–racial college students, there is a lack of longitudinal studies with multiple sources of discrimination as Latinos transition from high school (HS) to college. This study examined changes in peer, adult, and everyday discrimination across the college transition and tested concurrent, prospective, and reciprocal associations between these sources of discrimination, internalizing symptoms, and grade poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…Youths who exhibit more facility and comfort navigating multiple cultural resources and challenges before college may enter higher education with a greater foundation of social awareness, the ability to develop positive relationships with others, and skills to navigate different social contexts (Carbajal et al, 2022; Carlo et al, 2016). When faced with discrimination because of interpersonal, institutional, and structural forces (Aguirre, 2012; Castro et al, 2022), bicultural competence may be restricted across this transitional period. However, these same youths may leverage their bicultural abilities to respond to contextual demands, and behavioral bicultural competence established before entering college may particularly reduce internalizing psychopathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Youths who exhibit more facility and comfort navigating multiple cultural resources and challenges before college may enter higher education with a greater foundation of social awareness, the ability to develop positive relationships with others, and skills to navigate different social contexts (Carbajal et al, 2022; Carlo et al, 2016). When faced with discrimination because of interpersonal, institutional, and structural forces (Aguirre, 2012; Castro et al, 2022), bicultural competence may be restricted across this transitional period. However, these same youths may leverage their bicultural abilities to respond to contextual demands, and behavioral bicultural competence established before entering college may particularly reduce internalizing psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research has shown that youths of color encounter increasing perceived discrimination from professors but consistent peer discrimination as they progress grade levels (Del Toro & Hughes, 2020). Relying on the present study’s sample, prior work documented that discrimination from adults remains stable across the transition to college, whereas peer and everyday discrimination decrease from high school through college (Castro et al, 2022).…”
Section: Discrimination As a Concurrent Socio-contextual Risk Factormentioning
confidence: 95%
“…Cultural stressors, individually and collectively, have been shown to compromise mental health across a variety of indicators. Indeed, several studies have documented the detrimental impact of ethnic/racial discrimination across a number of indicators of adjustment (e.g., Castro et al, 2022; Cheng & Mallinckrodt, 2015). Similarly, numerous studies have indicated positive relations between bicultural stressors/stress 1 with depressive symptoms (e.g., Piña-Watson et al, 2019) and positive functioning (e.g., Meca, Webb, et al, 2022; Piña-Watson et al, 2019).…”
Section: Conceptualization Of Cultural Stressmentioning
confidence: 99%
“…Little research, however, has traced the full pathway from race‐based stressors, through stress responses, to academic achievement (see Figure 1). Previous work has linked discriminatory climates and school belonging to performance in math and reading among high school students (Baysu et al, 2022), and other studies have explored whether psychological distress from discrimination impacts Latine college students' academic performance (Castro, Sasser, Sills, & Doane, 2022; see also, Keels et al, 2017). Yet, there is no comprehensive research to date that has simultaneously considered social identity threat, psychological distress and physical stress in response to race‐based stressors and how they shape disparities in achievement among URM college students in STEM fields.…”
Section: The Present Researchmentioning
confidence: 99%